2021
DOI: 10.1021/jacs.1c03860
|View full text |Cite
|
Sign up to set email alerts
|

Efforts toward Further Integration of an Unnatural Base Pair into the Biology of a Semisynthetic Organism

Abstract: We have developed semisynthetic organisms (SSOs) that by virtue of a family of synthetic, unnatural base pairs (UBPs), store and retrieve increased information. To date, transcription in the SSOs has relied on heterologous expression of the RNA polymerase from T7 bacteriophage; here, we explore placing transcription under the control of the endogenous host multisubunit RNA polymerase. The results demonstrate that the E. coli RNA polymerase is able to transcribe DNA containing a UBP and that with the most optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 19 publications
(32 reference statements)
0
11
0
Order By: Relevance
“…Meanwhile, DNA polymerases in organisms are different from commercial DNA polymerases, so replication and transcription experiments in vivo are also necessary. , The effects of these nucleotides on physiology should be taken into account to build a healthier cellular system with unnatural nucleotides . To evaluate replication in vivo, the previously reported D6 containing dNaM flanked on each side by three randomized natural nucleotides was synthesized .…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, DNA polymerases in organisms are different from commercial DNA polymerases, so replication and transcription experiments in vivo are also necessary. , The effects of these nucleotides on physiology should be taken into account to build a healthier cellular system with unnatural nucleotides . To evaluate replication in vivo, the previously reported D6 containing dNaM flanked on each side by three randomized natural nucleotides was synthesized .…”
Section: Resultsmentioning
confidence: 99%
“…30,151 Recent in vivo experiments suggested that E. coli RNAP could also transcribe DNA containing some of these UBPs. 152 Recently, reverse transcription of RNA containing TPT3 or NaM has been investigated with several reverse transcriptases or DNAP mutants, including avian myeloblastosis virus (AMV) reverse transcriptase, Moloney murine leukemia virus (MMLV) reverse transcriptase, SuperScript II reverse transcriptase, SuperScript III reverse transcriptase, Super-Script IV reverse transcriptase, and an engineered Taq DNAP with reverse transcription activity, Volcano2G (V2G). 153,154 It was found that the UBP reverse transcription efficiencies of different reverse transcriptases were sharply different.…”
Section: Polymerases For the Synthesis Reverse Transcription And Repl...mentioning
confidence: 99%
“…acids (Zhang et al, 2017a;Zhang et al, 2017b;Fischer et al, 2020;Hashimoto et al, 2021;Manandhar et al, 2021), so we can confidently expect the broad application of unnatural components in future construction of nucleic acid scaffolds for building nanostructures and multi-enzyme machineries, both in vitro and in vivo.…”
Section: Author Contributionsmentioning
confidence: 99%